Penerapan Teori Patricia Benner dalam Proses Kredensial Keperawatan Ditinjau dari Sudut Pandang Filosofi di Rsud Kota Dumai - Ridwan, Junaina; Damanik, Siti Rahmalia Hairani (Jurnal Ners, 2025)
Introduction: Nursing credentials are a formal system that aims to assess and recognize the competence of nursing staff in providing care that meets professional standards. This process is not only legal and administrative, but also reflects the level of expertise and professional responsibility of a nurse. Objective: to analyze and understand the application of Patricia Benner’s Theory philosophy of "From Novice to Expert" in the nursing credential process. Research method: Qualitative descriptive with a case study approach, data collection was carried out through in-depth interviews, document searches and field observations, Results/findings: the implementation of nursing credentials at Dumai City Hospital has been implemented since 2015. With a total of 418 nursing staff with career levels PK I: 115 people, PK II: 114 people, PK 3; 80 people. BP 1: 23 people, BP 2: 44 people, BP 3: 36 people, while those who already have clinical authority according to career level PK 3: 38 people, PK 2: 21 people, and still on clinical authority PK1. Meanwhile, the number of midwives is BP 3: 7 people and BP 2: 3 people. Conclusion: The credential system at Dumai City Hospital has been implemented well, not only assessing the suitability of practice, but also fostering professionalism in a hierarchical, ethical manner, and adapting to field conditions